Purple Rosella (Hibiscus sabdariffa Linn.) Petal Extract Prevents Hepatocyte Degeneration in Wistar Rats Exposed to Cigarette Smoke - Ulilalbab, Arya; Wiratmadi, Bambang; Adriani, Merryana (Folia Medica Indonesiana, 2018)
Currently, the number of smokers in Indonesia is still high. Cigarette smoke contains free radicals. This study aimed to analyze the effects of purple rosella petal extract on the prevention of hepatocyte degeneration in Wistar rats exposed to cigarette smoke. Twenty male rats were divided into four groups: negative control, positive control, treatment group receiving 270 mg/kg BW purple rosella petal extract, and treatment group receiving 540 mg/kg BW purple rosella calyx extract. Negative control was only given with standard feed. Positive control was given with standard feed and exposed to 2 cigarettes a day. Treatment groups were fed with standard feed and administered with rosella extract in the morning then exposed to 2 cigarettes every day. This study was conducted for 28 days. At the end of the study, hepatocyte degeneration was observed in liver histopathology stained with hematoxilin eosin. The administration of purple rosella petal extracts in the doses of 540 mg/kgBW and 270 mg/kgBW significantly (p<0.05) prevented hepatocyte degeneration. Purple rosella petal extract is able to prevent hepatocyte degeneration in Wistar rats exposed to cigarette smoke.